Minimization of carryover for high‐throughput liquid chromatography with tandem mass spectrometry analysis of 14 mycotoxins in corn grits. Issue 13 (7th May 2014) - Tamura, Masayoshi; Matsumoto, Keiko; Watanabe, Jun; Iida, Junko; Nagatomi, Yasushi; Mochizuki, Naoki
<x xml:space="preserve">Abstract</x> A method for the simultaneous analysis of 14 mycotoxins with the minimization of carryover was developed. Our verification experiments suggested that the carryover occurred due to the chelation of fumonisins with the metal. To wash the fumonisins from the metal, the inner surface of the injection needle was rinsed with 10 mM trisodium citrate and 1% formic acid in water/methanol/acetonitrile/isopropanol after each injection, and the analysis was performed on a metal‐free Mastro C18 column. This approach remarkably minimized the carryover of fumonisins. Fourteen mycotoxins in samples were extracted with 2% acetic acid in water/acetonitrile and a quick, easy, cheap, effective, rugged, and safe extraction kit, purified on a MultiSep 229 Ochra, and then quantified by liquid chromatography with tandem mass spectrometry. Determinations performed using this method produced a linearity greater than 0.99 and recoveries ranging from 72.6 to 117.4%, with good intraday precision from 4.0 to 12.4%, and interday precision from 6.5 to 17.0%. The limits of detection ranged from 0.01 to 0.71 μg/kg, demonstrating that a highly sensitive method for the simultaneous analysis of mycotoxins over a wide range of concentrations was achieved with minimal carryover. When 12 samples of commercially available corn grits were analyzed with this method, deoxynivalenol, fumonisin B1, fumonisin B2, fumonisin B3, and zearalenone were present most frequently.